2015
DOI: 10.1039/c5gc00948k
|View full text |Cite
|
Sign up to set email alerts
|

CO2, COS and CS2 adducts of N-heterocyclic olefins and their application as organocatalysts for carbon dioxide fixation

Abstract: Various CO2, COS and CS2 adducts of N-Heterocyclic olefin (NHO) were synthesized and characterised by single crystal Xray crystallography. The length of C-O bond in NHO-COS adducts is slightly shorter than that in the corresponding NHO-CO2 adducts, while the C-S bond length in NHO-COS adducts is significantly longer than the corresponding C-S distance in the NHO-CS2 adducts, suggesting the negative charge of the NHO-COS adducts is preferentially delocalized on the sulfur atom. The length of the CCS2−CNHO bond … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(62 citation statements)
references
References 49 publications
2
60
0
Order By: Relevance
“…These reactions serve as the first examples of an N‐heterocyclic olefin (NHO) acting as an organic mediator for C−C bond‐coupling C ‐carboxylations of CH‐acidic positions by NHO‐activated CO 2 . A related C−O bond formation has been described by Wang and co‐workers who employed NHO–CO 2 adducts as catalysts for the O ‐carboxylation of propargylic alcohols and propylene oxides to obtain cyclic α‐alkylidene and propylene carbonates, respectively . The carboxylation of acetonitrile was also observed with a 1,3‐di‐ tert‐ butylimidazolium‐2‐carboxylate .…”
Section: Resultsmentioning
confidence: 64%
“…These reactions serve as the first examples of an N‐heterocyclic olefin (NHO) acting as an organic mediator for C−C bond‐coupling C ‐carboxylations of CH‐acidic positions by NHO‐activated CO 2 . A related C−O bond formation has been described by Wang and co‐workers who employed NHO–CO 2 adducts as catalysts for the O ‐carboxylation of propargylic alcohols and propylene oxides to obtain cyclic α‐alkylidene and propylene carbonates, respectively . The carboxylation of acetonitrile was also observed with a 1,3‐di‐ tert‐ butylimidazolium‐2‐carboxylate .…”
Section: Resultsmentioning
confidence: 64%
“…In summary, elegant studies from Lu and co‐workers and from Naumann, Thomas, and Dove have demonstrated the great synthetic potential of N‐heterocyclic olefins in promoting CO 2 fixation and polymerization processes. With their highly ylidic characters and inherently tunable structures, as observed with the parent NHC species, it is expected that NHOs will soon emerge as versatile organocatalysts for a much broader range of important Lewis/Brønsted base‐catalyzed reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Lu and co‐workers have recently reported the synthesis of a series of NHO–COS and NHO–CS 2 adducts for comparison to their previously synthesized NHO–CO 2 catalysts. These new catalytic systems were used to promote coupling reactions of CO 2 with epoxides (Scheme c).…”
Section: Co2 Sequestration Reactionsmentioning
confidence: 99%
See 2 more Smart Citations